Program Intervensi Berbasis Mindfulness untuk Meningkatkan Kesejahteraan Psikologis Caregiver Pasien Kanker Anak - Nur Baiti Astuti; Diana Setiyawati (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Diagnosis of cancer in children can be extremely stressful for the caregiver. The caregiver is “hidden patients” who have suffered from physical and psychological problems. However, only a few programs address the needs caregivers of children with cancer. This research aims to enhance psychological well-being (PWB) using mindfulness-based intervention for the caregiver. Participants of this study are 6 caregivers of children with cancer in Yayasan Kanker Anak Yogyakarta. The research design is one group of pretest-postest design. PWB scale used to measure caregiver’s well-being, given before treatment as a pre-test and after treatments as post-test. The descriptive statistic using Wilcoxon matched-pairs signed-ranks test showed improvements in psychological well being’s caregiver but were not statistically significant (Z= -1.051, p= 0.293 (p>0.05). However, caregivers had improved in self acceptance after mindfulness program (Z= -2.207, p= 0.016 (p< 0.05).